2020
DOI: 10.17977/um017v25i22020p088
|View full text |Cite
|
Sign up to set email alerts
|

Potensi timbulan sampah plastik di Kota Yogyakarta tahun 2035

Abstract: Plastic waste is the center of attention in urban areas in Indonesia, one of them is Yogyakarta. Yogyakarta is the largest wastes supplier in Piyungan's Integrated Waste Management Site. Piyungan decreases every year. Therefore, Yogyakarta Government must take appropriate steps to obtain waste generation in the future. This research aims to make a projection of plastic waste generation in Yogyakarta in 2035. The result of this research reveal the generation of plastic waste in Yogyakarta in 2035 based on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…One of the main impacts of tourism is the change in the generation rate and composition of municipal waste and household waste (Suryawan et al, 2021a). Several previous studies have reported an increase in waste generation in tourist areas due to the high number of tourists during the tourism season (Yusari and Purwohandoyo 2020;Nofriya et al, 2019;Pranata Darma;Rai Kristina 2021). Thus, the composition of waste and the level of waste generation can be different in places that are influenced by the social demographics of tourists and tourism destinations.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main impacts of tourism is the change in the generation rate and composition of municipal waste and household waste (Suryawan et al, 2021a). Several previous studies have reported an increase in waste generation in tourist areas due to the high number of tourists during the tourism season (Yusari and Purwohandoyo 2020;Nofriya et al, 2019;Pranata Darma;Rai Kristina 2021). Thus, the composition of waste and the level of waste generation can be different in places that are influenced by the social demographics of tourists and tourism destinations.…”
Section: Resultsmentioning
confidence: 99%
“…Padahal TPST Piyungan akan mengalami penurunan kapasitas daya tampung sampah seiring berjalannya waktu. Oleh karena itu, Pemerintah Kota Yogyakarta harus melakukan penanganan tertentu dalam mengantisipasi kemungkinan tingginya timbulan sampah plastik di Kota Yogyakarta di masa mendatang [16].…”
Section: Pendahuluanunclassified
“…Penelitian ini menggunakan pendekatan kuantitatif [14]. Pada tahap ini data yang didapat melalui TPSA Banyuurip berupa data pengangkutan volume sampah setiap hari yang dihasilkan di Kota Magelang.…”
Section: Dataset Timbangan Sampahunclassified